The Prevalence of Anemia in Elderly With Systolic Heart Failure - Sharareh Zeighami Mohammadi; Soolmaz Asgharzadeh Haghighi; Neda Falah (Sālmand, 2010)
Objectives: Anemia is prevalent in heart failures and is an independent risk factor for adverse clinical outcomes in patients with CHF. The aim of the present study was to determine the prevalence of anemia in elderly with systolic heart failure hospitalized in Alborz Hospital of Karaj in 2009.